An evaluate study on Rumah Tahan Sentara Asrama Bukit Baru, Malacca / Ooi Siew Sim - Ooi , Siew Sim (1987)
Juvenile delinquency has been on the increase in Malaysia since the last decade except for the drastic decrease in 1982. As one of the measure to counter this problem, the Ministry of Social Welfare has established institution to provide moral reformation and rehabilitation service to upgrade the academic and vocational capabilities of the delinquent juvenile. However, a juvenile delinquent is not a criminal and therefore, needs special treatment programme to guide and help them to change their anti social behaviour. In view of this, this study will evaluate the remand hostel as a rehabilitation and character reformation institution for the delinquents and its function to provide moral support from the delinquents. This study is based on the inmates of Rumah Tahansentera Asrama Bukit Baru in Malacca whose opinions are sought as o means to evaluate the effectiveness of the hostel in providing the necessary requirements needed for the students to change their delinquent way of life. The first part of Chapter One gives a very brief background of the social welfare services in Malaysia and the establishment of correction institution here. The research design for this study is also discussed in this chapter, namely its purpose, scope of study, method of data collection used and the problems encountered during fieldwork. Chapter Two, 'Definition of Concepts' introduces the necessary and fundamental concepts important for the under standing of t his study. The various views of a few social scientists who specialize in this field of study were taken. The writer feels it is undoubtedly helpful to be exposed to many different viewpoints. Subsequently, Chapter Three, gives an account of the Asrama Bukit Baru rehabilitation and reformation activities, the condition and procedure of admission to the hostel and the facilities provided by it. Various aspects of the hostel were also discussed, such as its objective, administration and the Juvenile Welfare Committee. Chapter Four explores and analyse the background of the student's respondents and the reasons that brought about their detention in the hostel. Aspects that are look into are their family background such as their relationship with their family members, forms of discipline at home and the family income. Also included for discussion in this chapter is the students relationship with their peers and their educational background. The writer feels that these factors have some influence on the students present behaviour and has important implication for how the delinquent will be viewed, treated, and handled by the administration for the treatment programme to be used most effectively. An evaluation on the effectiveness of the hostel is carried out in the fifth chapter. Concentration is placed on the students response towards the activities carried out, their relationship with the staff and their introduction with follow hostelmates. Finally, the last chapter ends with the conclusion of what have been discussed in this study. Suggestion by the writer to the hostel and issues that must be dealt with if the control, handling and treatment of the delinquent youngster is to be meaningful and effective are also discussed here.